2022
DOI: 10.1007/s00766-022-00391-7
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines adopted by agile teams in privacy requirements elicitation after the Brazilian general data protection law (LGPD) implementation

Abstract: The Brazilian General Data Protection Law (LGPD) implementation has impacted activities carried out by the software development teams. Due to it, developers had to become aware of the existing techniques and tools to carry out privacy requirements elicitation. Extending our previous work, we have investigated the actions taken by organizations regarding the LGPD, specifically in software development, considering the perception of agile development teams after two years of the LGPD implementation. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 73 publications
0
4
0
1
Order By: Relevance
“…Doe [74] shows a general discussion on the implementation of GDPR in the EU. Cordeiro [75] for Portugal, Mitrou [76] for Greece, Faifr and Januska [77] for the Czech Republic and Canedo et al [78] discuss the implementation of the LGPD in Brazil.…”
Section: G Rq4 -Challenges and Enablers For Miscellaneous Category (M...mentioning
confidence: 99%
“…Doe [74] shows a general discussion on the implementation of GDPR in the EU. Cordeiro [75] for Portugal, Mitrou [76] for Greece, Faifr and Januska [77] for the Czech Republic and Canedo et al [78] discuss the implementation of the LGPD in Brazil.…”
Section: G Rq4 -Challenges and Enablers For Miscellaneous Category (M...mentioning
confidence: 99%
“…In addition, we also identified that the documentation needs to be updated at each change of the software, also reported by Theunissen et al [Theunissen et al 2022] for the smooth running of projects. One of the participants mentioned that "the lack of specification of business requirements that impact legal requirements, such as the Brazilian General Data Protection Law (LGPD) [Canedo et al 2022, Canedo et al 2021 or General Data Protection Regulation (GDPR) [Aberkane et al 2021] may cause legal sanctions, such as changing legislation changing tax calculations or changing input/output layouts". Theunissen et al [Theunissen et al 2022] classified the information necessary for documenting the requirements in context and environment, which encompasses anything that affects the system but is not included in the primary goals, such as legal and environmental issues.…”
Section: Rq2 What Factors Influence Requirements Documentation and La...mentioning
confidence: 99%
“…Agile Privacy emphasizes transparency in data practices and gives users control over their personal data. This includes providing clear and easily accessible privacy notices, as well as giving users options to manage their data preferences (Canedo, et. al., 2022, Egieya, et.…”
Section: Understanding Agile Privacymentioning
confidence: 99%
“…Providing regular education and training for Agile teams on privacy best practices and compliance requirements is essential (Canedo, et. al., 2022, Olurin, et.…”
Section: Case Studiesmentioning
confidence: 99%